Análise comparativa entre os métodos construtivos de concreto armado e madeira em uma residência unifamiliar no Tocantins - Barbosa, Iutah Cristal Dezidério de Veras (Universidade Federal do Tocantins, 2020)
that can provide smaller dimensions and quantities of structural elements as a lower cost. Given this, it is believed that wooden structures can be a viable solution for building single-family homes, by combining concepts such as: good mechanical characteristics, reduced structure weight and construction time. Therefore, this work aims to perform a structural comparative analysis between the reinforced concrete and wood construction methods and also the comparative of cost with materials. Two structural projects were prepared, one in reinforced concrete and the other in wood, for a single-family residence consisting of two floors. From this, it was made the survey of the quantitative of structural elements and their dimensions, of the costs of the materials as available by Palmas-TO companies. The present work concluded that the wood construction system presented a reduction in the total weight of the structure, an increase in the number of pillars due to the limitations of the type of wood and sections available in the region and also that in terms of materials the structure of reinforced concrete showed a cost reduction .Therefore, this study showed some limitations presented by lumber, quantified the reduction of the weight of the structure and the cost of materials.